Pseudoaneurysm of uterine artery: as a cause of secondary post partum haemorrhage - Kodey, Prabha Devi; Koneru, Gangadhara Rao; Kota, Lakshmi Narayana; Kuchibatla, Sharada (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Secondary PPH is rare and life threatening, if the cause is not properly identified. Cases should be subjected for USG doppler to exclude rare entities such as pseudoaneurysm of uterine artery and AV malformations. Pseudoaneurysm of uterine artery is a rare entity to produce secondary PPH, but once identified can be effectively treated, provided facility of uterine artery embolisation is available. Methods: Here in we report 6 cases of secondary post partum haemorrhage where 5 were treated by uterine artery embolization, for recurrent attacks of bleeding following caesarean section with no identifiable cause and referred to our institution. We subjected them for USG doppler study - diagnosed to have pseudo aneurysm in 6 cases and further managed by angiography, followed by uterine artery embolisation. Results: Out of 6 cases, all cases were diagnosed of having pseudoaneurysm of either Right or Left uterine artery. 5 were subjected to uterine artery embolization. Out of the 5 cases, 4 responded well and in one case following coil embolisation as bleeding through collaterals still observed, hysterectomy had to be done. For 6th case because of haemodynamic unstability hysterectomy had to be done. Conclusions: Uterine artery embolization is an effective and reliable method for control of haemorrhage in pseudoaneurysm. One should have doubt about pseudoaneurysm in cases of secondary PPH where the bleeding is recurrent and cause not acertainable and to be referred in time where the facility of uterine artery embolization is available.